ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA TENTANG MATERI PELUANG - dila, oki ratna; ., Monalisa; Zanthy, Luvy Sylviana (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study aims to analyze the mathematical creative thinking ability of junior high school students in Cimahi with indicators used in opinion there are 4 components, namely fluency, flexibility, originality and elaboration. Finding different new ideas including mathematical creative thinking skills. This study uses a qualitative descriptive method. The instruments in the form of 5 items in the opportunity material were given to 30 students for research, one of the SMPs in Cimahi City. In this study it was found that mathematical creative thinking ability according to is included in the high category.